Analysis of an existing methodology for assessing vehicle-track interaction under reliability conditions - Djabbarov, Shuxrat; Bakhrom Abdullayev; Aziz Gayipov; Abdusaid Yuldashov; Nodir B. Adilov; Irina Soboleva (Sound & Vibration, 2026)
This paper presents a focused analytical audit of two simplified vehicle-track interaction schemes reported in the State Standard for 1,520 mm Gauge Railways: (i) a wheel-on-rail stability scheme intended to characterize flange-climb resistance and (ii) a track lateral stability scheme intended to estimate sleeper-rail-grid shift under train loading. The aim is twofold: first, to identify the internal inconsistencies of these specific formulations; second, to derive general lessons for transparent and reproducible safety assessment in railway engineering. The audit is organized around three steps: reconstruction of the source free-body diagrams and symbol definitions, point-by-point consistency checks of the equilibrium relations, and formulation of corrected self-contained equations in a unified coordinate system. The revised presentation shows that the source schemes mix force and moment terms, use ambiguous coordinate conventions, and in several places produce self-referential or physically trivial coefficients. A compact worked example is provided to illustrate the numerical difference between a parameter-independent source-style ratio and the corrected parameter-dependent contact-equilibrium relation. The paper also clarifies the status of each figure as either adapted from the source schemes or reconstructed by the authors and condenses the normative background to the material strictly needed for interpretation. Overall, the revised workflow improves traceability, reproducibility, and engineering interpretability.